Theranostic Microbubbles with Homogeneous Ligand Distribution for Higher Binding Efficacy - Simone A. G. Langeveld; Bram Meijlink; Inés Beekers; Mark Olthof; Antonius F. W. van der Steen; Nico de Jong; Klazina Kooiman (MDPI AG, 2022)
Phospholipid-coated targeted microbubbles are used for ultrasound molecular imaging and locally enhanced drug delivery, with the binding efficacy being an important trait. The use of organic solvent in microbubble production makes the difference between a heterogeneous or homogeneous ligand distribution. This study demonstrates the effect of ligand distribution on the binding efficacy of phospholipid-coated ανβ3-targeted microbubbles in vitro using a monolayer of human umbilical-vein endothelial cells and in vivo using chicken embryos. Microbubbles with a homogeneous ligand distribution had a higher binding efficacy than those with a heterogeneous ligand distribution both in vitro and in vivo. In vitro, 1.55× more microbubbles with a homogeneous ligand distribution bound under static conditions, while this was 1.49× more under flow with 1.25 dyn/cm2, 1.56× more under flow with 2.22 dyn/cm2, and 1.25× more in vivo. The in vitro dissociation rate of bound microbubbles with homogeneous ligand distribution was lower at low shear stresses (1-5 dyn/cm2). The internalized depth of bound microbubbles was influenced by microbubble size, not by ligand distribution. In conclusion, for optimal binding the use of organic solvent in targeted microbubble production is preferable over directly dispersing phospholipids in aqueous medium.